TUBERKULOSIS INTRAOKULAR (Nusantara Medical Science Journal, 2019)
Tuberculosis (TB) is an infectious disease caused by the bacteria, Mycobacterium tuberculosis. TB typically affects the lungs, but it can also affect other organs, including the eyes. Infection by Mycobacterium tuberculosis inside the eye is called intraocular TB. There are several controversies related to the terminology, diagnosis, and therapy that result in varying prevalence of intraocular TB, different selection of diagnostic tests, and different duration of Anti-TB therapies.
Keywords: choroiditis; immunology; infection; tuberculosis; uveitis